The assassin's curse - Sands, Kevin (Sands, Kevin. Blackthorn key adventure, 2018)
When Christopher Rowe's code-breaking uncovers the true target of an assassination attempt, he and his friends are ordered to Paris to investigate a centuries-old curse on the French throne.